Effects of Copper Stoichiometry on Cu(In, Ga)(S, Se)2 Thin-Film Solar Cells - Park, Sang Yeun; Min, Byoung Koun (한국화학공학회, 2026)
Copper stoichiometry governs the structural, electronic, and photovoltaic properties of Cu(In, Ga)(S, Se)2 absorbers. This review summarizes the effects of the Cu/(In + Ga) ratio on phase stability, defect thermodynamics, and band-edge modulation, and discusses how Cu control contributes to device performance. Under Cu-rich conditions, transient Cu2-x(Se, S) phases enhance grain growth but may cause metallic residues, while Cu-deficient compositions stabilize ordered vacancy compounds that improve p-type conductivity and interface alignment. At the electronic level, reduced Cu content weakens Cu-3d and (S, Se)-p coupling, lowering the valence band and widening the band gap by ~ 0.15–0.23 eV. An empirical Cu-dependent extension of the conventional band gap relation is presented to describe this effect. The optimum Cu/(In + Ga) range (0.85 ~ 0.95) ensures phase stability and minimal defect density, providing a basis for performance enhancement through composition and depth-controlled Cu grading.